Histogenesis of pro- and meso-nephroi in goat - Gopinath, S; Singh, Yashwant (The Indian Journal of Animal Sciences, 2012)
The process of histogenesis of the pronephros and mesonephros was recorded in goat embryos of 6 to 100 mm crown-rumplength (CRL), The functional pronephros were absent only an aggregation of mesenchymal tissue around preexistingpronephric duct at cranial ending of mesonephros represented its area in embryos of 6 mm CRL. The mesonephrosoccupied a large part of the coelomic cavity under the 7th to 21st body somites at this stage. Histological ditferentiation ofglomeruli and mesonephric tubules, into proximal and distal segments, evinced establishment of its excretory function by10 mm CRL. The glomeruli occupied entire cup of Bowman's capsule at 14 rom CRL. The degenerative changes inmesonephros progressed from 18 to 35 mm CRL crano-caudally. The proliferating mesenchymal tissue replaced thedegenerated structures by 85 mm CRL. Rarely 1-2 fragmented glomeruli could be seen in embryos of 100 mm CRL.